2019
DOI: 10.3390/su11247020
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Prediction of Minimum Miscibility Pressure (MMP) During CO2 Flooding Using Artificial Intelligence Techniques

Abstract: Carbon dioxide (CO2) injection is one of the most effective methods for improving hydrocarbon recovery. The minimum miscibility pressure (MMP) has a great effect on the performance of CO2 flooding. Several methods are used to determine the MMP, including slim tube tests, analytical models and empirical correlations. However, the experimental measurements are costly and time-consuming, and the mathematical models might lead to significant estimation errors. This paper presents a new approach for determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Then, the rest of the data (30%), which was unseen during the training stage, was used to evaluate the model performance. The use of 70 and 30% of the data for training and testing, respectively, was reported by several researchers; , therefore, we used these ratios in the current study. Moreover, several evaluation indices were used to evaluate the model’s reliability.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the rest of the data (30%), which was unseen during the training stage, was used to evaluate the model performance. The use of 70 and 30% of the data for training and testing, respectively, was reported by several researchers; , therefore, we used these ratios in the current study. Moreover, several evaluation indices were used to evaluate the model’s reliability.…”
Section: Methodsmentioning
confidence: 99%
“…This is the pressure at which the complete miscibility of oil and gas (or the pressure at which the mechanism of mixing displacement begins to be realized). There are experimental methods [65][66][67] and correlation formulas [68,69], and scientific work is underway to develop a calculation algorithm, through the use of artificial intelligence [70], to calculate the MMP. The use of artificial intelligence to calculate the MMP has reduced the average absolute error of calculations to 6.6%, whereas when calculating with correlation formulas, calculation errors can be 15-20% [70].…”
Section: Increasing Oil Recovery By Carbon Dioxide Pumped Into the Reservoirmentioning
confidence: 99%
“…MMP also can be considered as the minimum pressure at which the interfacial tension (IFT) between oil and injected gas tends to zero. , Therefore, it can be concluded that, in general, the pressure at which two phases are thoroughly mixed in each other is considered as MMP. There are various ways to estimate MMP, such as laboratory methods, using the equation of state (EOS), , empirical correlations, mathematical models, molecular dynamic (MD), , and artificial intelligence. It is necessary to mention that artificial intelligence methods for MMP estimation are divided into three groups, i.e., neural network, deep learning, and machine learning. It is worth emphasizing that none of these mentioned estimation methods are used alone to assess the MMP; instead, in one case, two or more of these methods will be used simultaneously for MMP estimation.…”
Section: Introductionmentioning
confidence: 99%